1990
DOI: 10.1111/j.1365-2958.1990.tb02010.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of divergent NtrA‐dependent promoters in the anaerobically expressed gene cluster coding for hydrogenase 3 components of Escherichia coli

Abstract: The regulatory region of two divergently oriented transcriptional units involved in the formation of the gas-evolving hydrogenase (isoenzyme 3) of Escherichia coli was investigated. DNA sequence analysis revealed the existence of a 210 bp non-coding region containing two sequences showing homology to -24/-12 NtrA-dependent promoters. These sequences were arranged in a divergent orientation entirely consistent with their being involved in transcribing the divergent operons. Through S1 protection experiments it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 41 publications
(30 reference statements)
1
36
0
Order By: Relevance
“…Previously, it was reported that in E. coli the expression offdhF (4) and various hydrogenase genes (6,18,30) required a functional ntrA. We have confirmed that fdhF expression in S. typhimurium also requires ntrA by using transposon insertional inactivation, i.e., introduction of ntrA209::TnlO.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Previously, it was reported that in E. coli the expression offdhF (4) and various hydrogenase genes (6,18,30) required a functional ntrA. We have confirmed that fdhF expression in S. typhimurium also requires ntrA by using transposon insertional inactivation, i.e., introduction of ntrA209::TnlO.…”
Section: Resultssupporting
confidence: 65%
“…In addi-* Corresponding author. tion, the transcription of several genes involved in the synthesis of active hydrogenase has been shown to require NtrA (4,6,18). Unlike the case with other enterobacterial sigma factors, activation of transcription by NtrA has been shown to require accessory, DNA-binding, trans-acting factors that bind to specific UASs that have many of the properties of eucaryotic enhancers (7,8,26).…”
mentioning
confidence: 99%
“…So far, only two divergently transcribed s 54 -dependent promoters have been characterized (Charlton et al, 1993;Lutz et al, 1990;Hopper et al, 1994). In Klebsiella pneumoniae, it has been reported that the IHF protein avoids activation of the nifJ promoter by NifA when it is bound to the UAS responsible for activating the divergently transcribed promoter nifH.…”
Section: Discussionmentioning
confidence: 99%
“…The release of FliA from the inhibitory action of FlgM is one of the most important check-points during flagella formation, and it occurs when FlgM is exported out of the cell once the hook-basal body structure is completed. Hence, it is tempting to speculate that cross-regulation mediated by these UASs helps keep these two proteins in equilibrium.So far, only two divergently transcribed s 54 -dependent promoters have been characterized (Charlton et al, 1993;Lutz et al, 1990; Hopper et al, 1994). In Klebsiella pneumoniae, it has been reported that the IHF protein avoids activation of the nifJ promoter by NifA when it is bound to the UAS responsible for activating the divergently transcribed promoter nifH.…”
mentioning
confidence: 99%
“…The genes are organized in two divergently transcribed operons (2,5,6). The hyc operon, transcribed in the counterclockwise direction, contains hydrogenase 3 structural genes (2), whereas the products of the clockwise-transcribed hyp genes pleiotropically influence the activities of all three hydrogenases of E. coli (6,10).…”
mentioning
confidence: 99%